DIFFERENCES IN CATCH RESULTS USING WIRE TRAPS WITH DIFFERENT BAITS IN LAKE KELARI, MUARO JAMBI VILLAGE - Aurelia Lutfiany; Lisna Lisna; Bs Monica Arfiana; Fahrizal Fahrizal; Fauzan Ramadhan; Putinur Putinur (Universitas Mataram, 2025)
This study aims to compare the fishing performance of wire traps (bubu kawat) using two different types of bait, namely oil palm fruit and coconut pulp, in Kelari Lake, Muaro Jambi. The research was conducted over a period of 20 days with two treatments and a total of 20 repetitions. Each treatment used 10 units of wire traps placed randomly at the study site. The observed parameters included fish species, number and weight of catches, and frequency of fish occurrence. The results showed that seven fish species were captured during the study, namely Nilem (Osteochilus vittatus), Kapiat (Puntioplites falcifer), Sebarau (Hampala ampalong), Tembakang (Helostoma temminckii), Gabus (Channa striata), Sepat (Trichopodus pectoralis), and Baung (Hemibagrus nemurus). Nilem was the most frequently caught species in both bait treatments, while Gabus had the lowest catch frequency. Statistically, there was no significant difference (P>0.05) in the number and weight of catches between the two bait types, although coconut pulp produced slightly higher catch numbers. Environmental parameters such as temperature, pH, and water depth were within the optimal range for freshwater fish, supporting the fishing activity. This study concludes that both bait types can be effectively used with wire traps, but oil palm fruit provides more consistent results for fishermen in Kelari Lake.